2013
DOI: 10.1002/srin.201200232
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Salt Tracer Amount on the Mixing Time Measurement in a Hydrodynamic Model of Gas‐Stirred Ladle System

Abstract: The hydrodynamic modeling method in gas‐stirred ladle system that widely used to measure the mixing time was reconsidered and discussed in this paper. The effect of injected salt tracer amount on the mixing time measurement was investigated. For the mixing time curve, the final concentration increased with the tracer amount increased; also this curve exhibited occasional sharp increasing tendency when a larger amount of tracer was injected. Besides, the obtained mixing time decreased with the tracer amount inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 20 publications
(15 reference statements)
1
16
1
Order By: Relevance
“…The salt solution tracer together with the conductivity method has become more and more popular nowadays. However, many researchers [19][20][21] have demonstrated the mixing time was indeed depending on the location of probe and tracer injection. Recently, Chen et al 21) studied the effect of salt tracer amount on the mixing time, which proposes that the tracer selection should be considered combined with the criterion of the definition of mixing.…”
Section: Modeling Of Gas-steel-slag Three-phase Flow In Ladle Metallumentioning
confidence: 99%
See 1 more Smart Citation
“…The salt solution tracer together with the conductivity method has become more and more popular nowadays. However, many researchers [19][20][21] have demonstrated the mixing time was indeed depending on the location of probe and tracer injection. Recently, Chen et al 21) studied the effect of salt tracer amount on the mixing time, which proposes that the tracer selection should be considered combined with the criterion of the definition of mixing.…”
Section: Modeling Of Gas-steel-slag Three-phase Flow In Ladle Metallumentioning
confidence: 99%
“…However, many researchers [19][20][21] have demonstrated the mixing time was indeed depending on the location of probe and tracer injection. Recently, Chen et al 21) studied the effect of salt tracer amount on the mixing time, which proposes that the tracer selection should be considered combined with the criterion of the definition of mixing. In addition, Conejo et al 22,23) reported the effects of slag properties (thickness and viscosity) and nozzle diameter on mixing phenomena in gas-stirred ladles by physical modeling, a negative effect of both slag thickness and slag viscosity on mixing time was found, and an increase in nozzle diameter decreases mixing time, but the effect is not significant.…”
Section: Modeling Of Gas-steel-slag Three-phase Flow In Ladle Metallumentioning
confidence: 99%
“…3. In most of the previous investigations, the mixing time was defined as a period for an instantaneous tracer concentration to settle within ±5% deviation around the final constant tracer concentration in the bath [10][11][12]. The present authors proposed another criterion based on the rate of tracer concentration change, namely mixing intensity criterion, which has been detailedly discussed in an earlier paper [9] and it is used herein to determine the mixing time.…”
Section: Definition Of Mixing Timementioning
confidence: 99%
“…At high gas flow rates, its effect can be neglected. Chen et al (2012Chen et al ( , 2013 reported that both, an increase in saturation concentration and tracer amount, decrease mixing time. This effect was attributed to higher buoyancy forces by the tracer.…”
Section: Effect Of Tracer Concentration On Mixing Timementioning
confidence: 99%
“…An important consequence of the previous results is that direct comparison of mixing times between different investigations in water modeling is complicated because there are too many variables involved in the definition of mixing time. Chen et al (2013Chen et al ( , 2012 reported that the concentration amount employed in a large number of investigations was in the range from 0.0076 10 -3 to 19.610 -3 . The huge difference in the amount of tracer employed in different experiments is expected to report large differences in mixing time.…”
Section: Effect Of Tracer Concentration On Mixing Timementioning
confidence: 99%